Analisis Soal dalam Buku Siswa Matematika Kurikulum 2013 Kelas VIII Semester I Berdasarkan Dimensi Kognitif dari TIMSS - Budi Cahyono; Nurul Adilah (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2016)
This study aimed to analyze the student math book of curriculum 2013 for first semester grades VIII Kemendikbud based on the cognitive dimension of the TIMSS. This report result based on the TIMSS that mathematical ability learners Indonesia is low, so that the government must assess the previous curriculum and impelementation curriculum of 2013. The method use a descriptive qualitative research. The subject is a matter of training and competence test questions each chapter in the book student math. The collection of data uses documentation. Guidelines for the analysis of matter based on the cognitive dimension of assessment framework of the TIMSS 2015. The results showes that 36 matter only reached the level of cognitive domain knowing with the percentage of 16.98%, 114 matter has reach the level of applying with the percentage of 53.77%, and 62 matter has reach the level of reasoning with the percentage of 29.25%.